The Contact-Hitting R&D Strategy of Family Firms in the Japanese Pharmaceutical Industry. (September 2019) - Asaba, Shigeru; Wada, Tetsuo
This article addresses the following question: How do family firms investing less in research and development (R&D) than nonfamily firms compete in R&D intensive industries? Using Japanese pharmaceutical industry data, we found that family firms produce more patents per R&D than nonfamily firms but are not biased toward low-value innovations. Further analyses of the distribution over innovation value suggested that family firms adopt a "contact-hitting R&D strategy, " avoiding radical innovations and pursuing incremental innovations compatible with their signature moves: innovation through tradition and narrow and internal search and resulting in may low-value innovations and a few mid or high-value innovations.